Evaluasi Penggunaan Obat Kemoterapi Pada Pasien Kanker Payudara Di RSUP Fatmawati Periode Februari 2021 - Haryani, Setianti (Jurnal Farmasi Klinik Best Practice, 2022)
Breast cancer is a malignancy that originates from glandular cells, glandular ducts and breast supporting tissues excluding breast skin (PerMenKes, 2018). Treatment of breast cancer can use chemotherapy drugs alone or a combination of several chemotherapy drugs. Chemotherapy drugs are given in stages, generally for 6-8 cycles so that the curative effect is achieved and the side effects received by the patient can be reduced. This study aims to evaluate the use of chemotherapy drugs in breast cancer patients at Fatmawati General Hospital for the period of February 2021. This research is a non-experimental type of research with a retrospective evaluative descriptive design from patient medical records and analyzed descriptively quantitatively. This research method used a descriptive design with retrospective observational data collection, namely by collecting medical record data from breast cancer patients, this study used purposive sampling and obtained 34 patients who met the inclusion criteria. The study showed that the most age of breast cancer patients who underwent chemotherapy at Fatmawati General Hospital in February 2021 were patients with an age range of 36-45 years, with 18 patients (52.94%), the most common type of chemotherapy drug regimen used was the CAF regimen (Cyclophosphamide + Doxorubicin + 5 FU) in 8 patients (23.53%), therapy with the CAF regimen was given starting from the patient's age in the late adult range (46-55 years) until past the late elderly (> 65 years), drug therapy with the CAF regimen as the first-line standard (first line) is the most widely used with doses according to the National Guidelines for Medical Services for Management of Breast Cancer and a deviation between 1-13%, other regimens a combination of Carboplatin and Paclitaxel in 5 patients (14.71%) with doses and deviations ranging from 0-79% more lower than the literature. Key words: Breast Cancer, Chemotherapy, Chemotherapy Drug Regimen, CAF, CEF